Smoking mediates the relationship between SES and brain volume: The CARDIA study - Dougherty, Ryan J.; Moonen, Justine; Yaffe, Kristine; Sidney, Stephen; Davatzikos, Christos; Habes, Mohamad; Launer, Lenore J. (PloS one, 2020)
Investigate whether socioeconomic status (SES) was related to brain volume in aging related regions, and if so, determine whether this relationship was mediated by lifestyle factors that are known to associate with risk of dementia in a population-based sample of community dwelling middle-aged adults. We studied 645 (41% black) participants (mean age 55.3±3.5) from the Coronary Artery Risk Development in Young Adults (CARDIA) study who underwent brain magnetic resonance imaging. SES was operationalized as a composite measure of annual income and years of education. Gray matter volume was estimated within the insular cortex, thalamus, cingulate, frontal, inferior parietal, and lateral temporal cortex. These regions are vulnerable to age-related atrophy captured by the Spatial Pattern of Atrophy for Recognition of Brain Aging (SPARE-BA) index. Lifestyle factors of interest included physical activity, cognitive activity (e.g. book/newspaper reading), smoking status, alcohol consumption, and diet. Multivariable linear regressions tested the association between SES and brain volume. Sobel mediation analyses determined if this association was mediated by lifestyle factors. All models were age, sex, and race adjusted. Higher SES was positively associated with brain volume (β = .109 SE = .039; p < .01) and smoking status significantly mediated this relationship (z = 2.57). With respect to brain volume, smoking accounted for 27% of the variance (β = -.179 SE = .065; p < .01) that was previously attributed to SES. Targeting smoking cessation could be an efficacious means to reduce the health disparity of low SES on brain volume and may decrease vulnerability for dementia.